2003
DOI: 10.1023/b:chro.0000005740.56221.03
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of ring bivalents in holokinetic systems: Alternative sites of spindle attachment in Pachylis argentinus and Nezara viridula (Heteroptera)

Abstract: Heteropteran chromosomes are holokinetic; during mitosis, sister chromatids segregate parallel to each other but, during meiosis, kinetic activity is restricted to one pair of telomeric regions. This meiotic behaviour has been corroborated for all rod bivalents. For ring bivalents, we have previously proposed that one of the two chiasmata releases first, and a telokinetic activity is also achieved. In the present work we analyse the meiotic behaviour of ring bivalents in Pachylis argentinus (Coreidae) and Neza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 22 publications
7
52
1
Order By: Relevance
“…Two m-chromosomes remain separated till diplotene, get associated subsequently to form a negatively heteropycnotic pseudobivalent that lacks chiasma and usually occupies centre of the plate as is also observed in other coreids (Sands 1982a, b andPapeschi et al 2003). At metaphase-I, a definite pattern of arrangement is observed in both the species.In Serinetha augur, the autosomes and single bipartite X are arranged in a circle, while m-pseudobivalent lies in the centre as is also observed in Ochrochira rubrotinita and Pachylis argentinus (Sands 1982a, b, Papeschi et al 2003.…”
Section: Coreidaesupporting
confidence: 68%
See 1 more Smart Citation
“…Two m-chromosomes remain separated till diplotene, get associated subsequently to form a negatively heteropycnotic pseudobivalent that lacks chiasma and usually occupies centre of the plate as is also observed in other coreids (Sands 1982a, b andPapeschi et al 2003). At metaphase-I, a definite pattern of arrangement is observed in both the species.In Serinetha augur, the autosomes and single bipartite X are arranged in a circle, while m-pseudobivalent lies in the centre as is also observed in Ochrochira rubrotinita and Pachylis argentinus (Sands 1982a, b, Papeschi et al 2003.…”
Section: Coreidaesupporting
confidence: 68%
“…Then after, Y becomes the lightest element of the complement as is also recorded in Coridius janus, Andrallus spinidens and Nezara viridula by Satapathy and Patnaik (1991). Papeschi et al (2003), however, observed both X and Y to be positively heteropycnotic till diakinesis in Nezara viridula.…”
Section: Discussionmentioning
confidence: 68%
“…In some Heteroptera, a single NOR was observed, which could be interstitial or terminal and located at autosomes or sex chromosomes (Camacho et al, 1985;Fossey and Liebenberg, 1995;González-García et al, 1996;Papeschi et al, 2003;Rebagliati et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, only 1 GC-rich heterochromatic block (interstitial or terminal) is recognized, which is often associated with the nucleolus organizer region (NOR; Camacho et al, 1985;Papeschi et al, 2003;Grozeva et al, 2004). Reports of interstitial heterochromatic blocks scattered throughout most autosomes are scarce and restricted to the family Curiae (Holhymenia rubiginosa and Spartocera batatas) (Fabricius, 1798) (Franco et al, 2006;Bressa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed the distribution of 18S rDNA sites in autosomal chromosomes, such as those observed in Pachylis argentinus Berg, 1879, and Nezara viridula Linnaeus, 1758 (Papeschi et al, 2003), as well as in sex chromosomes such as those of the families Belostomatidae , Cimicidae (Grozeva et al, 2010), and Reduviidae (Bardella et al, 2010). Although studies investigating the location of heterochromatin are more common in Heteroptera, most of them are restricted to conventional analyses such as C-banding technique .…”
Section: Introductionmentioning
confidence: 99%